PENGARUH SISTEM BLOK PRAKTEK TERHADAP KOMPETENSI MAHASISWA JURUSAN TEKNOLOGI PENGOLAHAN KULIT POLITEKNIK ATK YOGYAKARTA - Nurwantoro; Alfani Risman Nugroho (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2018)
Teaching factory is a learning model in vocational education institutions that uses a product (goods/services) as a learning media to delivering competency and organized through collaboration between school and industry. The block system is one of the main elements of the Teaching Factory learning method. Through a block system, the process of learning theory and practice is carried out alternately in sufficient time to fulfill the desired competencies. This study aims to determine the effect of the application of the practice block schedule in the learning process to increase the effectiveness of learning at the Leather Processing Technology Department, Polytechnic of ATK Yogyakarta, and to determine the effect of the application of the practice block schedule on improving student competency in the Leather Processing Technology Department, Polytechnic of ATK Yogyakarta. In proving and analyzing this, multiple linear regression analysis was used with the f test and t test. The numbers of samples in this study were 40 students who had graduated. Data collection techniques were by giving questionnaires to students, interviews and documentation. Testing data analysis used validity, reliability, classic assumption tests and linear regression tests. The results of the analysis test can be interpreted that the variable schedule system block practice subjects do not affect general competency. This was because the value of -t count> -t table (-0.004> -2.024) or significance> 0.05 (0.997> 0.05) so that Ho was accepted. To improve the competency of students or graduates there were several variables that can influence other than the block schedule there was still an adequate curriculum and infrastructure. However, the practice block system was able to increase the effectiveness of learning in the Leather Processing Technology Department, Polytechnic of ATK Yogyakarta in accordance with the answers of respondents. Respondents stated that they are very appropriate (15-25%), appropriate (40-60%) and quite appropriate (5-25%).